The glucocorticoid receptor is required for stress erythropoiesis - Bauer, Anton; Tronche, François; Kellendonk, Christoph; Reichardt, Holger Michael; Schütz, Günther (Genes & development, 1999)
The glucocorticoid receptor (GR) coordinates a multitude of physiological responses in vivo. In vitro, glucocorticoids are required for sustained proliferation of erythroid progenitors (ebls). Here, we analyze the impact of the GR on erythropoiesis in vivo, using GR-deficient mice or mice expressing a GR defective for transactivation. In vitro, sustained proliferation of primary ebls requires an intact GR. In vivo, the GR is required for rapid expansion of ebls under stress situations like erythrolysis or hypoxia. A particular, GR-sensitive progenitor could be identified as being responsible for the stress response. Thus, GR-mediated regulation of ebl proliferation is essential for stress erythropoiesis in vivo.
Gesehen am 18.02.2019